A5_3 Explosive Decompression: Trajectory Troubles - Macquillin, Jamie; Kerr, John; Musk, Jack; Priest, Isaac (Physics Special Topics, 2020)
In this paper we investigate and model the effects of an Explosive Decompression on the orbital trajectory of the International Space Station (ISS). We found that in an ideal, full decompression, the trajectory of the ISS would remain relatively unchanged, only affecting the altitude of perigee by 8 km.